The Female FTSE Board Report 2010: Opening up the Appointment Process - Vinnicombe, Susan; Sealy, Ruth; Graham, Jacey; Doldor, Elena (Cranfield University School of Management, 2010)
2010 saw another year of barely perceptible change in the representation of women in leadership positions of UK PLC’s top 100 companies. The incremental increases include three additional women on FTSE 100 boards taking the total to 116; one additional female executive director (ED); four more companies with women on their boards; and two more companies with more than one woman on the board, returning to 2008 levels. Overall, the percentage of women on FTSE 100 boards is 12.5%, showing a three year plateau. The number of companies with no female directors has decreased to 21 and the number of companies with more than one woman on the board has returned to the 2008 figure of 39. Only 13% of new appointments went to women.